Pembelajaran Agama Islam Kreatif Untuk Meningkatkan Karakter Siswa di SD N 09 2X11 Enam Lingkung - Sitto Rahmana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Character education plays a crucial role in shaping the personality of elementary school students. However, Islamic Religious Education (IRE) learning in elementary schools is still predominantly conventional and focuses mainly on cognitive aspects, resulting in limited internalization of moral values in students’ daily behavior. This community service program aimed to enhance students’ character through the implementation of creative Islamic Religious Education learning at SD Negeri 09 2X11 Enam Lingkung. The methods employed included Islamic digital storytelling, educational games, group discussions, and role-playing activities conducted in four structured learning sessions. The participants consisted of 20 fifth-grade students. Evaluation was carried out through character observation covering honesty, discipline, responsibility, and cooperation, supported by discussions with teachers. The results indicated an improvement in students’ character, with most students categorized as good in all observed indicators. Creative IRE learning increased students’ engagement, fostered positive attitudes, and helped students practice Islamic values in their daily lives. This program demonstrates that creative Islamic Religious Education learning is an effective approach to strengthening character education in elementary schools.